2010
DOI: 10.1007/s00449-010-0456-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and kinetic modeling of the start-up of a UASB reactor treating municipal wastewater at low temperature

Abstract: A kinetic modeling-based study was carried out to evaluate the start-up performance of a 10-L up-flow anaerobic sludge blanket (UASB) reactor treating municipal wastewater under different organic and hydraulic loading conditions. The reactor was operated for 105 days (around 4 months) below 20 °C and with three different hydraulic retention times of 24, 12 and 5 h. Imposed volumetric organic loading rates (OLR) ranged from 0.57 (±0.05) to 11.78 (±0.85) kg TCOD/m(3)-day. Although relatively high incoming volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 36 publications
1
16
1
2
Order By: Relevance
“…The determined values of kinetic parameters are in good agreement with the results reported by Isik and Sponza [4], who had performed the kinetic modelling of UASB reactor treating simulated textile wastewater. Turkdogan-Aydinol et al [31] have also reported the results of kinetic modelling of UASB reactor treating municipal wastewater at low temperature and found the values of U max and K B , respectively, as 1.996 and 1.536 g L −1 d −1 . The difference in the values of the kinetic parameters in the present study compared to Turkdogan-Aydinol et al [31] may be due to different operating conditions and characteristics of wastewater used.…”
Section: Reactor Performancementioning
confidence: 92%
See 1 more Smart Citation
“…The determined values of kinetic parameters are in good agreement with the results reported by Isik and Sponza [4], who had performed the kinetic modelling of UASB reactor treating simulated textile wastewater. Turkdogan-Aydinol et al [31] have also reported the results of kinetic modelling of UASB reactor treating municipal wastewater at low temperature and found the values of U max and K B , respectively, as 1.996 and 1.536 g L −1 d −1 . The difference in the values of the kinetic parameters in the present study compared to Turkdogan-Aydinol et al [31] may be due to different operating conditions and characteristics of wastewater used.…”
Section: Reactor Performancementioning
confidence: 92%
“…Turkdogan-Aydinol et al [31] have also reported the results of kinetic modelling of UASB reactor treating municipal wastewater at low temperature and found the values of U max and K B , respectively, as 1.996 and 1.536 g L −1 d −1 . The difference in the values of the kinetic parameters in the present study compared to Turkdogan-Aydinol et al [31] may be due to different operating conditions and characteristics of wastewater used.…”
Section: Reactor Performancementioning
confidence: 92%
“…7b. Comparable results were achieved by Aydinol et al (2011) for K B (0.08 g l À1 h À1 ) and m max (0.0625 g l À1 h À1 ) in a UASB reactor at OLR from 1.2 to 11.7 gCOD l À1 d À1 . The m max and K B were 0.14 and 0.19 g l À1 h À1 , in an up-flow anaerobic fixed film reactor at 30 C, at OLR of 0.18 and 3.16 gCOD l À1 d À1 , respectively treating formaldehyde contaminated wastewater (Raja Priya et al, 2009).…”
Section: Kinetic Modelingmentioning
confidence: 58%
“…A c c e p t e d M a n u s c r i p t 6 where, a=S i /k 2(S) .X and b is a constant greater than one. (S i -S)/S i expresses the substrate removal efficiency and is symbolized as RE.…”
Section: Performance Of the Two-stage Anaerobic Reactormentioning
confidence: 99%
“…Numerous mathematical models, such as Monod-type kinetic, First-order, Second-order, Grau et al., Stover-Kincannon, Contois, Chen and Hashimoto, Dewalle and Chian, Young and McCarty [4][5][6], have been applied to anaerobic processes to determine the importance of the relationship between the design data and experimental results [6]. Among these models, Stover-Kincannon model is the most widely used mathematical model for determining the kinetic constants in wastewater treatment systems [2,7] A c c e p t e d M a n u s c r i p t 3 types of wastewaters, such as poultry slaughterhouse wastewaters [2], soybean [5], starch [9] and synthetic [10,11].…”
Section: Introductionmentioning
confidence: 99%